Técnica alcoólica simplificada para a cimentação de pinos intrarradiculares pré-fabricados - Monize Ferreira Figueiredo de Carvalho (2018)
Effect of ethanol-wet bonding on retetion of post to root dentin Fiber post have been an alternative to cast metal posts due to the modulus of elasticity similar to dentin. However, one of the causes of failure is cement degradation. The ethanol-wet bonding was developed with the purpose of reducing this degradation and increasing the durability of bonding between dentin and cement. The aim of this in vitro study was to evaluate the mechanical properties of two resin cements and the respective bonding interface between root and dentin treated according to two cementation protocols. Bovine incisor teeth were used. The crowns were sectioned at the cemento-enamel junction and the roots received endodontic treatment and post space preparation. Prior to the cementation of fiberglass, roots were randomly divided according to root surface treatment: conventional technique and ethanol-wet bonding. Two types of resin cements were used to cement the posts: RelyXTM ARC / Scotchbond Multi-Purpose Plus (3M ESPE) and RelyXTM U200 (3M ESPE). After cementation, the roots were stored at 100% humidity at room temperature for seven days for scanning by computerized microtomography (micro CT) or for 24 hours and 1 year for push-out and scanning electron microscopy. For the analysis of micro CT, NRecon software was used to generate tridimensional images and CTan software analyzed the porosity percentage (%) in the luting line. The post-gel contraction (%) of the cements was measured using the strain gauge technique. For push-out test, the roots were sectioned and two specimens were obtained in each root third, with 1.0 mm of thickness each. The test used load cell of 5000N and speed of 0.5mm / min. The specimens were examined in stereoscope to identify the mode of fracture. Images obtained by scanning electron microscopy for the evaluation of the cement line. The effect of the factors under study and their interaction on percentage of porosities in the cementation line was verified by ANOVA and Tukey post-hoc test (p0.05). The postgel shrinkage was analyzed by Students t test and bond strength in the root thirds was verified by Kruskal-Wallis e Mann-Whitney test (p0.05). When evaluating the porosity in the cementation line, the ethanol-wet bonding with RelyXTM U200 presented the lowest values of porosity in the cementation line for the cervical and apical thirds. The RelyXTM U200 resin cement showed the lowest degree of post-gel polymerization shrinkage. Immediate bond strength values did not differ between groups and root thirds. However, storage for 12 months produced a negative effect. Despite this effect, the association between simplified ethanol wet-bonding with RelyXTM U200 exhibit better values of bond strength when compared the conventional protocol for this resin cement. It was concluded that RelyXTM U200 with ethanol wet-bonding had the lowest percentage of porosity in the cervical and apical thirds and RelyXTM U200 resin cement showed the lowest degree of post-gel polymerization shrinkage.